Zumba Preference and Its Cardiovascular Endurance Intensification - Laroza, Alvy; Piral, Lovely; Palcis, Melissa Joy; Calixtro, Vivencio L. (Indonesian Journal of Teaching in Science, 2021)
The purpose of this study is to determine the level of preference of recorded video and live demonstration Zumba in terms of instructions, movements, and concepts. It also determines the significant difference between cardiovascular endurance intensification of respondents in recorded video and lives demonstration Zumba in terms of frequency, intensity, time, and type. This study used the descriptive-evaluative design with the survey questionnaire to 30 respondents. The demographic profile of the respondents implies that most of the Zumba enthusiasts are aged 20-25 years old. Women are more likely to participate than men with a normal Body Mass Index. The level of preference of recorded video Zumba has a descriptive rating of High extent which is interpreted as highly satisfied. On the contrary, the level of preference of recorded video Zumba has a descriptive rating of high extent which is interpreted as highly satisfied. The cardiovascular endurance intensification in recorded video Zumba has a descriptive rating of high extent which is interpreted as highly intensified. Meanwhile, the cardiovascular endurance intensification in live demonstration Zumba has a descriptive rating of high extent which is interpreted as highly intensified. Moreover, there is no significant difference between the recorded video and live demonstration Zumba. In addition, there is no significant difference between Cardiovascular Endurance Intensification in recorded video and Live demonstration Zumba. This research can contribute to the workout modalities of the people who are willing to be physically fit in a form of dance exercise which is commonly known as “Zumba”.